Hans Gerstner (1851-1939) in koncept nacionalne glasbene kulture - Weiss, Jernej (De musica disserenda, 2010)
This contribution focuses on the activities of Hans Gerstner, one of the most prominent musicians to have come to Slovenia from the Czech lands. The recent discovery of Gerstner's diary has led to the re-examination of his life and work, in particular the question of the adequacy of some later music history interpretations of musical developments in the second half of the nineteenth and the early twentieth century in Slovenia. These primarily followed the so-called concept of national music culture. This has revealed a growing need for the reinterpretation of certain chapters of musical history from the period concerned.
Keywords: Gerstner, Hans, 1851-1939; glasba; music; češki glasbeniki; zgodovina glasbe; Slovenia; Slovenija